2018 Development effectiveness review. (Mandaluyong City Asian Development Bank, 2019)
In line with recent development progress in Asia and the Pacific, ADB development effectiveness is assessed and areas where ADB performance needs to be strengthened are identified.
Keywords: Asian Development Bank; Economic development projects -- Management; Economic development projects -- Evaluation